Pengaruh Variasi Konsentrasi Sukrosa pada Formulasi Gummy Candies Sari Buah Belimbing Wuluh Kombinasi Lemon sebagai Produk Nutraceutical - Chandra, Muhammad Andi; Alfina, Sophia; Dewi, Citra Kharisma; Pinanggi, Alfasyah Oktarini Pinanggi; Nur Mulia, Shilfa Nadira; Nurlifa, Mya; Chandra, M. Andi (Universitas Borneo Lestari, 2025)
Lemon and starfruit are fruit plants used in traditional medicineThe purpose of this study was to determine how differences in sugar content affected the way gummy candy was made. This study's methodology included the creation of five different gummy sweets using starfruit juice and lemon. Physical quality assessments, such as organoleptic testing, pH, weight uniformity, elasticity tests, water content tests, and hedonic tests, were also conducted. The study's findings demonstrated that the gummy sweets' flavor became sweeter with increasing sugar content. As can be seen, formula 5 has the maximum sucrose content at 1.5 grams. The conclusion reached is that changes in the amount of sucrose used as a sweetener may affect the preparation's physical quality evaluation test results as well as the respondent's hedonic test evaluation. It was discovered that formula 2 and 4, which included 0.5 grams and 0,2 grams of sucrose, was the one that responders liked the best.